Architectural Landmarks Illustrating a Territory as Seen in Ancient Art Exhibitions between the 19th and 20th Centuries in Italy and Beyond - Camporeale, Elisa (Lo sguardo rinnovato, 2026)
This essay examines how architecture was narrated and displayed in temporary exhibitions between the late 19th century and the First World War, with a special eye for ancient art exhibitions of the early 1900s, where painting, sculpture, and decorative arts were also represented. The study explores the role and importance assigned to cities as a whole and to civic and religious buildings, as well as the media chosen to depict and disseminate them: drawings, photographs, paintings, prints, architectural models, and even organized visits or excursions. It also considers how exhibitions constructed a sense of place: in the United States and Germany, through large photographs and three-dimensional models, and in Italy, through historical-topographical approaches. Together, these case studies reveal the ways in which exhibitions contributed to shaping cultural identities by identifying regional landmarks with both natural and human-made landscapes.